SCIENTIFIC AND THEORETICAL BASES OF DEVELOPING THE CULTURE OF TOLERANCE IN HIGHER EDUCATION BIOLOGY TEACHERS (Conferencea, 2024)
It is considered an interesting and purposeful step for the formation of tolerance attitudes of teachers and the Prevention of professional pedagogical changes. After all, understanding oneself as a person who is not tolerant/intolerant represents the first step towards overcoming them, while acknowledging the existence of professional changes.